CRYSTALLIZATION OF MICROLITES AND DEGASSING DURING MAGMA ASCENT: CONSTRAINTS ON THE FLUID MECHANICAL BEHAVIOR OF MAGMA DURING THE TENJO ERUPTION ON KOZU ISLAND, JAPAN - Noguchi S.; Toramaru A.; Shimano T. (My University, 2006)
Bubble and crystal textures provide information with regard to the kinetics of the vesiculation and crystallization processes. They also provide insights into the fluid mechanical behavior of magma in a conduit. We performed textural (bubble and crystal) and compositional analyses of pyroclasts that were obtained from the Tenjo pyroclastic flow, which resulted on account of the eruption in 838 A.D. on Kozu Island, about 200 km south of Tokyo, Japan. Pyroclasts in one flow unit (300∼2,060 kg/m3 ; average density 1330 kg/m3 ) can be classified into three types on the basis of vesicle textures. Type I pyroclasts have small isolated spherical bubbles with higher vesicularities (67–77 vol.%) and number density (10.8–11.7 log m−3 ). Type II pyroclasts have vesicularities similar to type I (61–69 vol.%), but most bubbles exhibit evidences of bubble coalescence, and lower number densities than type I (8.9–9.5 log m−3 ). Type III pyroclasts contain highly deformed bubbles with lower vesicularities (16–34 vol.%) and number densities (8.2–9.0 log m−3 ).
Keywords: Microlite crystallization; Degassing; Textural analysis; Crystal size distribution; Vesicle textures; Conduit flow